STRATEGI PERUMUSAN VISI, MISI, DAN TUJUAN PESANTREN YANG RESPONSIF TERHADAP TANTANGAN PENDIDIKAN ABAD KE-21 - Rheina Sayla; Isnaini Sapitri; M.Yasir Ardiansyah; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Islamic boarding schools as Islamic educational institutions in Indonesia face major challenges in maintaining their relevance and sustainability in the tumultuous educational era of the 21st century. To remain responsive to social dynamics, technology and globalization, the formulation of vision, mission and goals is crucial in guiding the direction and aspirations of these institutions. This qualitative research reveals that progressive and adaptive Islamic boarding schools formulate their vision not only as guardians of religious and cultural values, but also as educational centers that prepare students with relevant skills for the digital era and globalization. Their vision integrates religious values with an emphasis on creativity, critical thinking, and digital literacy. The mission of Islamic boarding school education is not only limited to religious teaching, but also includes the development of moral character, ethical values, and practical life skills. Through comprehensive curriculum development and the integration of technology in the learning process, Islamic boarding schools ensure that the education they provide remains relevant to the demands of the times, preparing students to face global challenges such as technological advances and intense job market competition. The specific goals of Islamic boarding schools include improving academic achievement, building moral character, and preparing students to face global challenges. Pesantren implementation strategies focus on diverse extracurricular programs, partnerships with industry for practical experience and internships, as well as the effective use of information technology in the teaching and learning process. These strategies improve the quality of education provided by Islamic boarding schools and prepare students to become highly moral and competent members of a global society in an era that continues to change rapidly. By understanding and adopting best practices in formulating vision, mission and goals, Islamic boarding schools can play an important role in educating generation.